Getting back on track: Forecasting after extreme observations - Pål Boug; Håvard Hungnes; Takamitsu Kurita (Statistics Norway, Research Department, 2024)
This paper examines the forecast accuracy of cointegrated vector autoregressive models when confronted with extreme observations at the end of the sample period. It focuses on comparing two outlier correction methods, additive outliers and innovational outliers, within a forecasting framework for macroeconomic variables. Drawing on data from the COVID-19 pandemic, the study empirically demonstrates that cointegrated vector autoregressive models incorporating additive outlier corrections outperform both those with innovational outlier corrections and no outlier corrections in forecasting post-pandemic household consumption. Theoretical analysis and Monte Carlo simulations further support these findings, showing that additive outlier adjustments are particularly effective when macroeconomic variables rapidly return to their initial trajectories following short-lived extreme observations, as in the case of pandemics. These results carry important implications for macroeconomic forecasting, emphasising the usefulness of additive outlier corrections in enhancing forecasts after periods of transient extreme observations.
Keywords: C32; C53; E21; E27; 330; Extreme observations; additive outliers; innovational outliers; cointegrated vector autoregressive models; forecasting